2014
DOI: 10.1371/journal.pone.0115398
|View full text |Cite
|
Sign up to set email alerts
|

Directional Secretory Response of Double Stranded RNA-Induced Thymic Stromal Lymphopoetin (TSLP) and CCL11/Eotaxin-1 in Human Asthmatic Airways

Abstract: BackgroundThymic stromal lymphoproetin (TSLP) is a cytokine secreted by the airway epithelium in response to respiratory viruses and it is known to promote allergic Th2 responses in asthma. This study investigated whether virally-induced secretion of TSLP is directional in nature (apical vs. basolateral) and/or if there are TSLP-mediated effects occurring at both sides of the bronchial epithelial barrier in the asthmatic state.MethodsPrimary human bronchial epithelial cells (HBEC) from control (n = 3) and asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
(78 reference statements)
2
27
1
1
Order By: Relevance
“…912 The VIRAL cohort is a longitudinal study of children admitted to the hospital with suspected viral respiratory infections. W1 was taken during acute RV infection as confirmed by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…912 The VIRAL cohort is a longitudinal study of children admitted to the hospital with suspected viral respiratory infections. W1 was taken during acute RV infection as confirmed by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…These results provide further evidence that RV can induce a type 2 cytokine response that could result in an exaggerated allergic immune response and thereby exacerbations in asthmatic individuals. Less is known concerning the role of TSLP following RV infection, although studies have reported increased levels of TSLP in nasal secretions from asthmatics infected with RV that was not seen in noninfected nonasthmatics [66, 67]. …”
Section: Innate Immune Response To Rhinovirusmentioning
confidence: 99%
“…Clinically defined phenotypes include nonatopic wheezers, viral-induced asthma or multitrigger wheezers that may differentially respond to treatment or may even undergo spontaneous remission and therefore require personalized therapy (10). In fact, rhinovirus infection-induced asthma exacerbations in children were associated with elevated TSLP and CCL-11 (eotaxin-1) levels that can be noninvasively detected in nasal secretions (11). The repeated report of genetic associations of IL-33 and TSLP (12) with asthma risk is particularly interesting as TSLP, IL-25 (IL-17E) and IL-33 (13) are considered to play a role in the early commitment towards Th2 immunity and type 2 innate (ILC2) lymphocytes (14).…”
mentioning
confidence: 99%